OP0156-HPR COST EFFECTIVENESS OF TELE-HEALTH FOLLOW-UP IN RHEUMATOID ARTHRITIS BASED ON A NON-INFERIORITY RANDOMIZED CONTROLLED TRIAL. (2nd June 2020) - De Thurah, A.; Skovsgaard, C.; Maribo, T.; Hjøllund, N. H.; Kruse, M.
Abstract : Background: The clinical effectiveness of a patient-reported outcome (PRO) based telehealth intervention offered to rheumatoid arthritis (RA) patients with low disease activity or remission has previously been reported 1 . The TeRA study showed that PRO-based telehealth follow-up in RA achieved similar disease control as conventional outpatient follow-up among patients with low disease activity or remission. The degree of disease control did not differ between telehealth follow-up offered by rheumatologists or rheumatology nurses. Objectives: To compare the cost-effectiveness of PRO–based telehealth follow-up to patients with RA performed by rheumatologists or rheumatology nurses with conventional outpatient follow-up. Methods: A total of 294 patients were randomized (1:1:1) to either PRO-based telehealth follow-up carried out by a nurse (PRO-TN) or a rheumatologist (PRO-TR), or conventional outpatient follow-up by physicians. Quality of life (EQ-5D) was measured at baseline and at follow-up after one year. The primary outcome was a change in the Disease Activity Score, C-reactive Protetin in 28 joints (DAS-28, CRP). The focus in the health economic evaluation was on the relation between costs and EQ-5D in the period between one year prior to and one year after the intervention. All costs were measured at the individual level and consisted of: intervention costs, health and social care costs, and productivity costs. All cost data were retrieved from Danish population-based registers. Incremental cost-effectiveness rates (ICERs) were calculated on the basis of a comparison of the development in costs and effects in the two intervention groups (separately and combined) with the control group. Bootstrap with 10, 000 replications were used to access significance. Results: The difference in health and social care costs during the intervention period compared to the year before were €1, 072, - €50 and €519 for the control group, the PRO-TR group and the PRO-TN respectively. Hence, the change in health and social care costs was lower for both intervention groups. The PRO-TR group had a small decrease and it was significantly lower than for the control group (p=0.0027). The difference between health and social care costs in the PRO-TN group compared to the control group was only borderline significant (p=0.067). No statistically significant differences were found in QALY's between the three groups, all three groups experienced minor, non-significant, declines in QALY over the intervention period. ICER's were not statistically significant but below known threshold values for the PRO-RN group (ICER=€17, 121). Conclusion: It is difficult to obtain statistically significant results for cost-effectiveness in small samples. However, the results point towards a possible cost-saving impact of PRO interventions in patients with low disease activity or remission. The study was unable to conclude if PRO-TR or PRO-TN were most cost-effective. Other relevant considerations, like patient satisfaction or organisational issues, should determine the way of organizing RA disease management in these patients. References: [1]de Thurah A, Stengaard-Pedersen K, Axelsen M, et al. Tele-Health Follow-up Strategy for Tight Control of Disease Activity in Rheumatoid Arthritis: Results of a Randomized Controlled Trial. Arthritis care & research 2018; 70 (3): 353-60. Disclosure of Interests: Annette de Thurah Grant/research support from: Novartis (not relevant for the present study)., Speakers bureau: Lily (not relevant for the present study)., Christian Skovsgaard: None declared, Thomas Maribo: None declared, Niels Henrik Hjøllund: None declared, Marie Kruse: None declared